2002
DOI: 10.1103/physreve.66.036140
|View full text |Cite
|
Sign up to set email alerts
|

First- and second-order phase transitions in scale-free networks

Abstract: We study first-and second-order phase transitions of ferromagnetic lattice models on scalefree networks, with a degree exponent γ. Using the example of the q-state Potts model we derive a general self-consistency relation within the frame of the Weiss molecular-field approximation, which presumably leads to exact critical singularities. Depending on the value of γ, we have found three different regimes of the phase diagram. As a general trend first-order transitions soften with decreasing γ and the critical si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
108
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(123 citation statements)
references
References 28 publications
(33 reference statements)
4
108
1
Order By: Relevance
“…Kaplan, Hinczewski, and Berker [22] reported that in the presence of quenched disorder the ordered phases are still robust and persist for the entire range of disorder. Recently, Iglói and Turban [37] have considered a mean-field version of the Potts model and reported that an order/disorder transition solely occurs for γ > 3. A q(γ) can then be defined above which the order of the transition changes from second-to first order, like on periodic lattices.…”
Section: B Transfer Matrixmentioning
confidence: 99%
“…Kaplan, Hinczewski, and Berker [22] reported that in the presence of quenched disorder the ordered phases are still robust and persist for the entire range of disorder. Recently, Iglói and Turban [37] have considered a mean-field version of the Potts model and reported that an order/disorder transition solely occurs for γ > 3. A q(γ) can then be defined above which the order of the transition changes from second-to first order, like on periodic lattices.…”
Section: B Transfer Matrixmentioning
confidence: 99%
“…Thus, they show that for the same scale-free networks, different algorithms give different results. The q-state Potts model has been studied in scale-free networks by Igloi and Turban [13] and depending on the value of q and the degree-exponent γ first-and second-order phase transitions are found, and also by Lima [15] on directed BA network, where only first-order phase transitions have being obtained independent of values of q for values of connectivity z = 2 and z = 7 of the directed BA network. More recently, Lima [14] simulated the Ising model for spin S = 1 on directed BA network and different from the Ising model for spin S = 1/2, an unusual order-disorder phase transition of order parameter was seen; this effect needs to be re-evaluated in the light of the time dependence presented below.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we consider this case first and then the case x = 1. i) When x = K 4 /K 2 = 1, the two species of spin are indistinguishable. Then, m ∼ M and the AT model is reduced to the four-state Potts model [13]. Expanding the free energy density (2) up to the third order in m gives…”
mentioning
confidence: 99%